The Value of Oxygen Desaturation Index for Diagnosing Obstructive Sleep Apnea: A Systematic Review. (25th April 2020) - Rashid, Nur HA; Zaghi, Soroush; Scapuccin, Marcelo; Camacho, Macario; Certal, Victor; Capasso, Robson
Abstract : Objectives: Intermittent hypoxemia is a risk factor for developing complications in obstructive sleep apnea (OSA) patients. The objective of this systematic review was to identify articles evaluating the accuracy of the oxygen desaturation index (ODI) as compared with the apnea–hypopnea index (AHI) and then provide possible values to use as a cutoff for diagnosing adult OSA. Study Design: Systematic Review of Literature. Methods: PubMed, the Cochrane Library, and SCOPUS databases were searched through November 2019. Results: Eight studies (1, 924 patients) met criteria (age range: 28–70.9 years, body mass index range: 21.9–37 kg/m 2, and AHI range: 0.5–62 events/hour). Five studies compared ODI and AHI simultaneously, and three had a week to months between assessments. Sensitivities ranged from 32% to 98.5%, whereas specificities ranged from 47.7% to 98%. Significant heterogeneity was present; however, for studies reporting data for a 4% ODI ≥ 15 events/hour, the specificity for diagnosing OSA ranged from 75% to 98%, and only one study reported the positive predictive value, which was 97%. Direct ODI and AHI comparisons were not made because of different hypopnea scoring, different oxygen desaturation categories, and different criteria for grading OSA severity. Conclusion: Significant heterogeneity exists in studies comparing ODI and AHI. Based on currently published studies, consideration should be given for diagnosing adult OSA with a 4% ODI of ≥ 15 events/hour and for recommending further evaluation for diagnosing OSA with a 4% ODI ≥ 10 events/hour. Screening with oximetry may be indicated for the detection of OSA in select patients. Further study is needed before a definitive recommendation can be made. Laryngoscope, 131:440–447, 2021